Reproductive biology, morphology and diet of Raja straeleni (spotted skate) in South Africa - Azevedo, Alexandra (Department of Biological Sciences, 2023)
The spotted skate, Raja straeleni, is the most abundant and frequently caught skate in the waters of southern Africa. This study aims to add information on the morphology, reproductive biology and feeding habits of R. straeleni in southern Africa to better manage the species and to understand its role in the ecosystem. Samples were obtained from trawlers operating on the west and south coasts of South Africa during 2020. A total of 72 skates ranging in total length (LT) from 392 to 695 mm were examined. The 19 males ranged from 437 to 630 mm and the 53 females ranged from 392 to 695 mm. The following relationships were quantified (1) disk width (D)=0.77LT-11.96, (2) D=0.94Length to first dorsal-14.66, (3) male weight Wmale = 3.61LT-22.74, (4) Wfemale = 3.32LT-20.85. The length-at-50% maturity (L50) of the males was estimated at 57.1 cm (95% confidence interval: 54.2-59.4 cm), or 91% of the maximum male length recorded in this study. The total length-at-50% maturity (L50) of the females was estimated at 62.5 cm (95% confidence interval: 57.0-64.0 cm), or 90% of the maximum female length recorded in this study. Adult skates were collected during a period of sexual dormancy, as deduced from the low sperm presence and lack of oocytes. The diet of 57 skates were examined of which four had empty stomachs two contained only unidentifiable remains. Prey items spanning six phyla were recorded. In terms of %frequency they were Arthropoda (17%), Chordata, (8.2%), Mollusca (4.5%), Echinodermata (1.9%), Annelida (1.9%), and Nemertea (1.9%). The trophic level of R. straeleni was 3.98 ±0.05 SE. The trophic level was previously calculated as 3.74 (n = 421) (Ebert and Bazzarro 2007). The difference in findings is a result of a higher incidence of squid in the diet of skates examined in this study. The average trophic level of Raja species is 3.76 (n = 12, 95% Cl = 3.71 to 3.80), and for all skates it is estimated at 3.78 ±0.05 SE (n = 60) (Ebert and Bazzarro 2007). The diet of R. straeleni is very similar to that of other skates. Approximately 1000 t are landed per annum, predominantly from the inshore Agulhas Bank, which suggests a standing biomass at least ten times this amount (Attwood et al. 2011). R. straeleni, like other skates, is an important generalist carnivore in the Benguela system.